MOTIVASI DAN KOMPETENSI BERPENGARUH TERHADAP KINERJA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA - Sartika, Umi (Fakultas Ekonomi Universitas IBA, 2017)
The purpose of this research is to know the influence of motivation and competence toemployee performance of Tax Service Office Pratama Prabumulih. Population of thisresearch as many as 72 employees and the data was obtained from 58 respondent in TaxService Office Pratama Prabumulih. The analysis which used in this research is multiplelinier regression analysis, F test and t test. The result of calculations using SPSS, showedthat: determinant coeficient of 0.166 or 16.6%, illustrates that performance of employees(Y), can be explained by motivation and competence 16.6%, while the remaining 83.4%can be explained by other factor which are not include in this study. From the resulthypothesis F test, obtained value of Fcompute (5.460)> Ftable (2.78), means that there isthe influence of motivation and competence together to employee performance. Whileresult of the hypothesis t test, showed that application of motivation and competencepartially had influence to employee performance of Tax Service Office PratamaPrabumulih.